1977
DOI: 10.1002/cpt1977216675
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alprenolol on hemodynamic and metabolic responses to prolonged exercise in subjects with hypertension

Abstract: In 7 young men with essential hypertension, central and regional hemodynamics and leg metabolism were studied at rest, during and after a prolonged exercise, and with and without long-term alprenolol treatment. Alprenolol (200 mg twice daily) lowered arterial blood pressure. Heart rate decreased in relation to plasma levels during and after exercise. Cardiac output was not significantly influenced, but leg blood flow was reduced at rest. Lipolysis was also attenuated by treatment both at rest and during exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Other studies have not demonstrated a reduction in Q with PB during submaximal exercise (Frisk-Holmberg et al 1977;Wilmore et al 1985).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Other studies have not demonstrated a reduction in Q with PB during submaximal exercise (Frisk-Holmberg et al 1977;Wilmore et al 1985).…”
Section: Introductionmentioning
confidence: 93%
“…PB has been found to have variable effects on plasma Lametabolism during submaximal exercise. Some studies have demonstrated no change in plasma [La-] (Frisk-Holmberg et al 1977;Lundborg et al 1981;Van Baak et al 1987); other studies have found a decrease (Verstappen and Van Baak 1987). Muscle [La-] during submaximal exercise does not appear to be significantly altered by @B (Kaiser et al 1985;Frisk-Holberg et al 1979).…”
Section: Eflects On Glycolysismentioning
confidence: 99%
See 1 more Smart Citation
“…p-adrenoceptor antagonists are believed to decrease glycogenolysis in skeletal muscle by inhibiting phosphorylase activity (Haugaard & Hess, 1965). Decreased glycogenolysis can explain the reduced release of lactate from skeletal muscle during p-adrenoceptor blockade (Trap-Jensen, Clausen, Noer, Larsen, Krogsgaard & Christensen, 1976;Frisk-Holmberg, Jorfeldt & Juhlin-Dannfeldt, 1977;Juhlin-Dannfeldt & Astrom, 1979;Hartling et al, 1980). Furchgott (1959) felt unable to classify the receptors for catecholamine-induced glycogenolysis as either a-or p-adrenoceptors and proposed that the adrenoceptor responsible for glycogenolysis should be denoted the 'yreceptor'.…”
Section: Discussionmentioning
confidence: 97%
“…Thus impaired tissue lipolysis, by Pl-adrenoceptor blockade, may reduce the availability of free fatty acids for aerobic glycolysis (Trap-Jensen etal., 1976), this being reflected by reductions in the respiratory quotient (Epstein et al, 1965;Kaiser, 1984) indicating that carbohydrate metabolism may become predominant. Impairment of hepatic and muscle glycogenolysis by P2-adrenoceptor blockade (Arnold et al, 1968) may also reduce anaerobic glycolysis and explain the reported reductions of plasma lactate (Trap-Jensen et al, 1976;Frisk-Holmberg et al, 1977). Muscle lactate, however, is unaltered during 13-adrenoceptor blockade indicating that impaired performance is not the result of lactate accumulation .…”
mentioning
confidence: 99%